A Training Program to Develop Concepts and Skills Related to Occupational Health and Safety Issues for Workers in Photovoltaic Power Plants - Hamdy Hafez; Marwa El-Baz; Ahmed Elbasaty; Hilmy Awad (Port Said Journal of Educational Research)
The fundamental reason for the existence of risks and even the occurrence of most accidents is the factor itself, so it was necessary to train workers to fully adhere to prevention methods, apply precautionary measures for potential risks, spread preventive health awareness, how to manage work risks, and the importance of implementing regulations and legislation for occupational safety and health. So, the current research aims to propose a training program for the development of concepts and skills related to occupational health and safety issues for workers in the installation of photovoltaic power plants. To achieve this goal, the researchers prepared a list of occupational safety and health concepts and skills, identified the general objectives of the program, then designed the general framework of the proposed training program related to occupational safety and health, prepared an achievement test and an Observation card. The training program and tools were applied to the research group, and the results indicated that there were statistically significant differences between the mean scores of the experimental group in the achievement test in the pre and post-measurements in favor of the post-measurement. In addition, there were statistically significant differences between the mean scores of the experimental group in the observation card of skills related to occupational safety and health in the pre and post-measurements in favor of the post-measurement.